Analysis of asymmetric price transmission of selected vegetables in Peninsular Malaysia - Mohamed, Zainal Abidin; Illiyasu, Abdullahi (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
The wholesalers are practicing strategic pricing behavior in Malaysian vegetables markets to the extents that increase in the farm products prices were not fully transmitted to farmers as decrease, resulting to marketing inefficiency and loss of farmer’s income. Thus, the study aims to examine the existence of asymmetric price transmission (APT) in the vegetables supply chain of Peninsular Malaysia. Monthly data on farms, retails, and wholesale prices of two selected vegetables (Mustard and Spinach) for the period of ten years were sourced from federal agricultural marketing authority (FAMA). The data were analysis using Houck model to investigate for APT. The findings shows that relationship along the supply chain of selected vegetables were bidirectional. However, the results indicates that wholesale price reacts faster on price increase than price decrease to the changes made by farmers. On the other hand, farm prices response faster on price decrease than price increase as wholesaler change their prices. Besides, a long run estimation of price transmission for both vegetables revealed that wholesaler increases their price more than changes made by either retailers or farmers. Thus, the findings suggested that wholesalers exert market power in the vegetable industry.